An Empirical Research on the Relationship between Policy Uncertainty and Corporate Investment in China - QIU, MENGYA (2018)
Economic policy is the essential tool for the government to intervene and guide the national economy. This paper reviews the research and development related to the impact of economic uncertainty on corporate investment. From the perspective of economic policy uncertainty, this paper combines existing research and adopts the China economic policy uncertainty index jointly released by Stanford University and the University of Chicago to analyse the impact of this particular uncertainty on Chinese enterprises' investment. The research results show that policy uncertainty, in general, has an inhibiting effect on business investment, especially during periods of high economic instability. Further studies have found that non-state-owned enterprises are more sensitive to policy uncertainty than state-owned enterprises. Also, the index has different impacts on enterprises among regions with varying levels of development, with the eastern part are most vulnerable, followed by the central area and the western having the smallest impact. This study provides a reference for the Chinese government to formulate economic policies. The government needs to consider the complex implications of policy uncertainty under different circumstances when using economic methods to promote the development of corporates.